Zoonotic Diseases Situation in Nigeria; Control Measures and Challenges - Clement A. Meseko; Wilson J. Bertu; Ishaya S. Tekki; Ismaila Shittu; Amyel M. Gusi; Sunday E. Hambolu; Tony M. Joannis; David Shamaki; Reuben A. Ocholi (The Proceedings of the Nigerian Academy of Science, 2022)
Infectious diseases are responsible for illness, deaths and economic losses in human and animals. The situation is worse in developing countries with limited resources, poor infrastructures and technology necessary for disease prevention and control. Consequently, causative agents of diseases may emerge from animal reservoirs and are transmitted from animals to human as zoonoses or sustained human-to-human transmission may occur. About 60% of infectious diseases are zoonotic and over 75% of emerging and re-emerging diseases in human are acquired from animal hosts. Globally and in Nigeria, zoonotic diseases previously controlled such as yellow fever, Orthopoxvirus (monkey pox virus), Lassa fever, anthrax etc. are re-emerging and new ones like Avian influenza, Ebola, and respiratory coronaviruses (SARS, MERS and 2019-nCoV) are emerging. In addition, the transboundary nature and inter-continental introductions of many of these pathogens threaten the national economy and public health. Other zoonotic diseases like rabies, brucellosis and bovine tuberculosis are intractable due in part to negligence. Hence, the burden of zoonotic diseases in Nigeria is high and unabated despite available preventive vaccination for a disease like rabies. Some of these important zoonoses are discussed in detail in this paper with emphasis on effective control through the application of modern technology for surveillance, early and accurate diagnosis, biosecurity and preventive vaccination. These tools are however insufficiently deployed in Nigeria. It is therefore imperative to prioritise public health policies with focus on research, development and innovations for better impact on human and animal health with sequelae on national transformation.